PENERAPAN CATATAN AKTIFITAS FISIK, DIET, ISTIRAHAT & KELOLA STRESS PADA IBU RUMAH TANGGA DI RT.2 RW.4 GAYUNGAN, SURABAYA - Kurniawan, Afif; Mamesah, Marline Merke; Geonarso, Roberto A (PPM STIKES Adi Husada, 2023)
Introduction & Aim: This PPM activity is motivated by the high incidence of non-communicable diseases such as cardiovascular disease. The epidemiological transition of this disease describes a tendency towards degenerative diseases which is determined by people's behavior. Based on a survey conducted in RT 2 RW 4, Gayungan, Surabaya City, most of the residents suffer from high blood pressure. High blood pressure is a type of cardiovascular disease. The aim of this activity is to provide education on healthy lifestyles to avoid the risk of contracting CHD to residents. Method of Activity: This community service is carried out by providing education about cardiovascular disease and its prevention. At the end of the education, being given a notebook of daily activities can be a motivation to continue to behave in a healthy way to manage stress. Results: This activity was carried out on Jl. Dukuh Menanggal RT 2 RW 4 Gayungan sub-district, Surabaya City. Education is provided through PowerPoint media, leaflets, and daily recording sheets to improve healthy living and manage stress. After being given counseling, the level of knowledge of residents increased. To be able to implement what they have learned, residents are provided with personal notes as a reminder to live healthily. Discussion: survey results show that the majority of residents still lack regular physical activity. Cardiovascular disease is prone to attack people who lack physical activity. Physical exercise and sports activities will increase cardiac output, redistribution of blood flow, and reduce cholesterol and blood fat levels. Eating foods with balanced nutrition, as well as fruit and vegetables can provide additional vitamins, antioxidants, and fiber that the body needs. Conclusion living a healthy lifestyle with regular physical activity and eating more fruit and vegetables can avoid degenerative diseases.